Analisis Pengaruh Variabel Produk, Harga, dan Promosi Terhadap Keputusan Konsumen Pada Pembelian Handphone "Cross" di Sukoharjo - Yuniati, Neneng (Graduasi: Jurnal Bisnis & Ekonomi, 2014)
The purpose of this study was to determine the effect of product quality, price and promotion to purchases Cross handphone either partially or simultaneously, and know the most dominant factor influence on the purchase of âCross handphonesâ in Sukoharjo. Using multiple regresion analysis, F test, t test, the results of a study of 100 consumers, proving that there is simultaneously a positive and significant influence between product quality, price and promotion on purchase decisions. Partially positive and significant influence purchasing decisions contained in the price and promotion, where the price is the most dominant factors that influence on purchasing decisions. With the above results, it is expected the company always pay attention to pricing strategies, namely at an affordable price, the suitability of the price with quality products, competitive price and features. For product quality should be improved by adding features, more easily repaired, the model is more up to date and durable. For promotion company is expected to always promote âCross Handphoneâ by improving the quality of the promotion in an attractive form of advertising that consumers are curious and raises interest to buy